The influence of the behavioural inhibition system on the development of PTSD-like symptoms after presentation of a traumatic film in healthy subjects - Aram Kehyayan; Pia Wright; Jessica Marks; Jan-Martin Matura; Nikolai Axmacher; Stephan Herpertz; Henrik Kessler (European Journal of Psychotraumatology, 2023)
Background: The Behavioural Inhibition System (BIS) as a neural system controlling motivation and behaviour, has previously been linked to multiple mental disorders, including Post-traumatic Stress Disorder (PTSD). BIS-sensitivity could increase the likelihood of PTSD development after trauma. However, previous studies have largely measured BIS-sensitivity retrospectively (i.e. after trauma, or even after onset of PTSD). Objective: The study aims to confirm the relationship between BIS-sensitivity prior to trauma and PTSD symptoms. Method: After assessment of BIS-sensitivity, N = 119 healthy participants watched a film with visually disturbing material. After 72 h, participants completed a questionnaire on PTSD-related symptoms (PCL-5). Results: In a multiple linear regression model, BIS-sensitivity significantly predicted PTSD symptoms, even after controlling for the decrease in mood, as well as for participants’ age and sex, two factors that had previously been shown to influence BIS-sensitivity. Conclusions: This is the first study to measure BIS-sensitivity before the occurrence of the (experimental) trauma and strengthens its role as a potential pre-traumatic risk factor.